PENGARUH STANDARISASI LAPANGAN SPESIFIKASI PERSENJATAAN DALAM MENDUKUNG PENGELOLAAN TUGAS POKOK SATUAN DI JAJARAN TNI AD - Siswanto, Dwi Joko; M. Sigit Saksono; Jarwono; Silitonga, Frangky; Titiek Herawati; Sopiin; Sermatutar Felik Leandro; Sermatutar Muhamad Andre Nuralam R (JURNAL MAHATVAVIRYA, 2024)
The development of the weapons industry at this time, the country of Indonesia is growing rapidly both weapons from domestic products and purchases appropriated by the TNI, so that in order to address these conditions, the TNI must immediately formulate standardization of shooting ranges according to KSU and weapon specifications, so that the standardization of shooting ranges can be used as a means of testing,, weapons and munitions that are really reliable and tested for accuracy, in order to realize professional soldiers, with the aim of research to determine the effect of standardization of shooting ranges in order to improve the management of shooting training units in the ranks of the TNI, the planned research methodology. research methods. this research method uses according to. Wiratna Sujarweni (2014: 39) quantitative research is a type of research that produces discoveries that can be achieved (obtained) by using statistical procedures or other means of quantification (measurement). that the weapon specifications are greater than the standardization of the firing range, it can be concluded that the weapon specifications have a greater influence on the achievement of the main task of the army than the standardization of the firing range. so that the standard firing range is very influential segnifikan achievement of the main task of the ranks of the army, thus the hypothesis that states the standardization of the Firing Range has a significant effect on the achievement of the main task of the army is accepted